Inspiring a Broader Socio‐Hydrological Negotiation Approach With Interdisciplinary Field‐Based Experience. Issue 4 (6th April 2018) - Massuel, S.; Riaux, J.; Molle, F.; Kuper, M.; Ogilvie, A.; Collard, A‐L.; Leduc, C.; Barreteau, O.
Abstract: Socio‐hydrology advanced the field of hydrology by considering humans and their activities as part of the water cycle, rather than as external drivers. Models are used to infer reproducible trends in human interactions with water resources. However, defining and handling water problems in this way may restrict the scope of such modeling approaches. We propose an interdisciplinary socio‐hydrological approach to overcome this limit and complement modeling approaches. It starts from concrete field‐based situations, combines disciplinary as well as local knowledge on water‐society relationships, with the aim of broadening the hydrocentric analysis and modeling of water systems. The paper argues that an analysis of social dynamics linked to water is highly complementary to traditional hydrological tools but requires a negotiated and contextualized interdisciplinary approach to the representation and analysis of socio‐hydro systems. This reflection emerged from experience gained in the field where a water‐budget modeling framework failed to adequately incorporate the multiplicity of (nonhydrological) factors that determine the volumes of withdrawals for irrigation. The pathway subsequently explored was to move away from the hydrologic view of the phenomena and, in collaboration with social scientists, to produce a shared conceptualization of a coupled human‐water system through a negotiated approach. This approach changed the way hydrological research issues were addressed and limited the number of strong assumptions needed for simplification in modeling. The proposed socio‐hydrological approach led to a deeper understanding of the mechanisms behind local water‐related problems and to debates on the interactions between social and political decisions and the dynamics of these problems. Plain Language Summary: This paper provides a collective reflection on the ways to articulate an understanding of social dynamics within hydrological approaches, based on interdisciplinary experience gained in the field in North Africa. Fundamentally, the socio‐hydrological approach proposed here enabled a better understanding of the mechanisms behind human‐water dynamics and hence of the impacts of social and political decisions on future changes. The major shift in this interdisciplinary approach is that it provides evidence that things do not simply interact in a positive or negative way, but also combine and shape together. So we need to look for pragmatic ways to link the analysis of social dynamics with the understanding of the hydrological processes. This requires hydrology to open up further to different approaches and methods used in other scientific disciplines, especially human sciences. This could lead to a radically innovative way of conceiving and representing coupled human‐water systems. Key Points: In socio‐hydrology, modeling frameworks for coupled human‐water systems are currently designed by hydrologists These frameworks have axiological and epistemological limitations to integrating social dynamics A negotiation approach enables to apprehend the mutual shaping of the relations between water and society